2023
DOI: 10.3788/col202321.100201
|View full text |Cite
|
Sign up to set email alerts
|

Rydberg electromagnetically induced transparency in 40K ultracold Fermi gases

Guoqi Bian,
Biao Shan,
Lianghui Huang
et al.

Abstract: We report the measurement of the electromagnetically induced transparency (EIT) with Rydberg states in ultracold 40 K Fermi gases, which is obtained through a two-photon process with the ladder scheme. Rydberg-EIT lines are obtained by measuring the atomic losses instead of the transmitted probe beam. Based on the laser frequency stabilization locking to the superstable cavity, we study the Rydberg-EIT line shapes for the 37s and 35d states. We experimentally demonstrate the significant change in the Rydberg-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…It is shown that the atomic numbers of 87 Rb and 40 K decrease simultaneously at each stage of the evaporation in the crossed ODT, and the atoms 87 Rb still exist even the number of 40 K atoms is at its maximum, which ensures that we can obtain a standard atomic sample number by optimizing all steps in the ODT. Nearly N = 2.6 × 10 6 ultracold 40 K atoms 063402-3 are prepared at a temperature of 0.35 T F during the process of sympathetic cooling with 87 Rb, where T F = h ω is the Fermi temperature, [57] ω = (ω x ω y ω z ) 1/3 2π × 80 Hz is the geometric mean of the optical trap in our experiment, N is the particle number of 40 K atoms, and k B is Boltzmann's constant. As we decrease the intensity of the ODT step by step shown in Fig.…”
mentioning
confidence: 99%
“…It is shown that the atomic numbers of 87 Rb and 40 K decrease simultaneously at each stage of the evaporation in the crossed ODT, and the atoms 87 Rb still exist even the number of 40 K atoms is at its maximum, which ensures that we can obtain a standard atomic sample number by optimizing all steps in the ODT. Nearly N = 2.6 × 10 6 ultracold 40 K atoms 063402-3 are prepared at a temperature of 0.35 T F during the process of sympathetic cooling with 87 Rb, where T F = h ω is the Fermi temperature, [57] ω = (ω x ω y ω z ) 1/3 2π × 80 Hz is the geometric mean of the optical trap in our experiment, N is the particle number of 40 K atoms, and k B is Boltzmann's constant. As we decrease the intensity of the ODT step by step shown in Fig.…”
mentioning
confidence: 99%